Integration of Islamic Religious Education with Environmental Education in Building Ecological Ethics of Students - Mohammad Ramli (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
This study aims to analyze the integration of Islamic Religious Education with Environmental Education to develop ecological ethics among students at Hidayatullah Junior High School, Batam. This study uses a descriptive qualitative approach with a case study design, collecting data through in-depth interviews, participant observation, and documentation of teachers, principals, and students. The results show that the integration of Islamic Religious Education and Environmental Education at SMP Hidayatullah Batam is realized through Islamic values-based learning linked to environmental conservation, including teaching environmental-themed verses of the Qur'an, an eco-friendly school program, and Clean Friday activities. The implementation of this integration positively affects the development of ecological ethics among students, as reflected in their increased concern for environmental cleanliness, energy conservation, and active involvement in environmental conservation activities. Islamic values such as amanah (trust), ihsan (kindness), and khalifah fil-ardh (vicegerent) provide a spiritual foundation that strengthens students' ecological behavior. Supporting factors such as school commitment, community support, and parental participation are key factors in maintaining the sustainability of the integration program. This educational model can serve as a reference for developing Islamic education with an ecotheological perspective, relevant to the current challenge of global environmental degradation.